2010
DOI: 10.1073/pnas.1005061107
|View full text |Cite
|
Sign up to set email alerts
|

Newborn infants learn during sleep

Abstract: Newborn infants must rapidly adjust their physiology and behavior to the specific demands of the novel postnatal environment. This adaptation depends, at least in part, on the infant's ability to learn from experiences. We report here that infants exhibit learning even while asleep. Bioelectrical activity from face and scalp electrodes was recorded from neonates during an eye movement conditioning procedure in which a tone was followed by a puff of air to the eye. Sleeping newborns rapidly learned the predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 47 publications
6
70
0
Order By: Relevance
“…Pitch violations and sensory dissonance in music excerpts, as in Perani et al (36), similarly led to a profound reduction of BOLD signal changes. This finding is noteworthy because it corresponds with the finding that a newborn's brain can adapt its neurophysiology to specific biological input, which makes learning from experiences possible (40). This adaptation is arguably crucial for language acquisition.…”
Section: Discussionsupporting
confidence: 72%
“…Pitch violations and sensory dissonance in music excerpts, as in Perani et al (36), similarly led to a profound reduction of BOLD signal changes. This finding is noteworthy because it corresponds with the finding that a newborn's brain can adapt its neurophysiology to specific biological input, which makes learning from experiences possible (40). This adaptation is arguably crucial for language acquisition.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, it is noteworthy that active (or REM) sleep occupies the biggest portion of a child's sleep and occurs much earlier in human development than proper dreaming (Foulkes 1993). Altogether, these data suggest that REM sleep of infants is likely to subserve crucial emotional (Berger et al 2012;Perogamvros 2012) and learning functions (Fifer et al 2010), much like what is found in adults (Sterpenich et al 2009;Wagner et al 2001) (see Sect. 3.5).…”
Section: Emotional Maturationmentioning
confidence: 59%
“…Indeed, Fifer and colleagues [101] showed that new associative reflexes like conditioned eyeblink responses can be readily acquired in infants while sleeping. It remains to be elucidated to what extent the putative down-states of cerebellar neurons at the various sleeping stages directly affect acquisition and consolidation of procedural memories [40].…”
Section: Box 3 Theoretical Models Explaining Sleep-dependent Memory mentioning
confidence: 99%